2008
DOI: 10.1016/j.sleep.2007.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation in non-obese children with obstructive sleep apnea

Abstract: Systemic inflammation is a constitutive component and consequence of OSA in many children, even in the absence of obesity, and is reversible upon treatment in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
115
0
10

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(136 citation statements)
references
References 46 publications
11
115
0
10
Order By: Relevance
“…Furthermore, it has been shown that SDB has an independent additive effect on the inflammatory changes caused by overweight and obesity in children and adolescents (6). Results of the inflammatory markers at baseline in this report are consistent with the effects of SDB (8,9). However, the lowering of the hs-CRP levels was not linked to improvements in either sleep or anthropometric parameters.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Furthermore, it has been shown that SDB has an independent additive effect on the inflammatory changes caused by overweight and obesity in children and adolescents (6). Results of the inflammatory markers at baseline in this report are consistent with the effects of SDB (8,9). However, the lowering of the hs-CRP levels was not linked to improvements in either sleep or anthropometric parameters.…”
Section: Discussionsupporting
confidence: 86%
“…In examining these results the following statements need to be considered. It is known that both obesity and SDB induce a low-grade systemic inflammatory response (6)(7)(8)(9)22,23). Furthermore, it has been shown that SDB has an independent additive effect on the inflammatory changes caused by overweight and obesity in children and adolescents (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is one of the strongest risk factors for developing OSAS (3,4). Meanwhile, clinical and fundamental studies suggest that inflammation involves the pathogenesis of OSAS (5)(6)(7)26,27) and IL-6 was reported to phenotypically increase in patients with OSAS (28)(29)(30). In an attempt to elucidate the relationship between genetic variants in the IL-6 gene and OSAS, we provided two aspects of support with a population-based study.…”
Section: Discussionmentioning
confidence: 91%
“…In particular, the activation of inflammatory pathways by OSA has emerged as a possible important contributor to end organ injury associated with this disorder, perhaps especially in the presence of concomitant obesity [46][47][48]. The role of a systemic inflammatory process in OSA is supported by findings of increased C-reactive protein (CRP) and IL-6 levels and lower IL-10 levels in children with OSA, which has been reported to improve following adenotonsillectomy [49][50][51] and one month of nasal CPAP therapy. However, data is mixed regarding CRP improvement after adenotonsillectomy in obese children with OSA [6,52].…”
Section: Sleep Disordered Breathingmentioning
confidence: 99%